Fear of Missing Out (FoMO) and Student Consumer Behavior: Financial Inclusion or Digital Debt Trap? - Hamin, Dewi Indrayani; Podungge, Robiyati (Journal of International Conference Proceedings, 2025)
This study investigates the effects of psychological and cognitive factors such as Fear of Missing Out (FoMO), financial literacy, self-control, and digital financial risk awareness on the consumer behavior of Indonesian university students. A quantitative method was used, applying Structural Equation Modeling with Partial Least Squares (SEM PLS), based on data collected from 450 students at Universitas Negeri Gorontalo who use digital financial services. The results show that FoMO does not significantly influence consumer behavior (p = 0.985), while self-control and financial literacy are stronger predictors of spending patterns. Additionally, the use of digital financial services is negatively associated with impulsive buying (p = 0.002, ? = -0.1323), indicating that these platforms may support better financial management. Rather than falling into a digital debt trap, students appear to experience financial inclusion when supported by adequate financial knowledge and strong self-regulation. The findings suggest that improving financial literacy alone is insufficient. Educational initiatives should also incorporate behavioral strategies such as emotional regulation and awareness of digital financial risks to encourage responsible financial behavior among digitally active youth.